Role of HRCT Scan of Chest in the Evaluation of COVID-19 Pneumonia (TAJ: Journal of Teachers Association, 2021)
Coronavirus disease (COVID-19) pneumonia emerged in Wuhan, China, in December 2019. It is a highly contagious viral disease spreading worldwide, with a rapid increase in the number of cases & deaths. COVID-19 pneumonia is characterized by fever, fatigue, dry cough, and dyspnea with other systemic features such as diarrhea, altered sensorium, stroke & multi-organ failure. HRCT chest is one of the most sensitive modalities for early detection of COVID-19 pneumonia & monitor the outcome of these patients. It is an important complement to the reverse transcriptase polymerase chain reaction (RT-PCR) tests. HRCT shows high specificity & sensitivity in detection of COVID-19 pneumonia being 90.7% & 70.8% respectively. In this pandemic situation, proper diagnosis & management of COVID-19 positive cases largely depends on HRCT findings & severity scoring.TAJ 2021; 34: No-1: 109-114